2015
DOI: 10.1017/s2040174415001105
|View full text |Cite
|
Sign up to set email alerts
|

Embryos, DOHaD and David Barker

Abstract: The early embryo and periconceptional period is a window during which environmental factors may cause permanent change in the pattern and characteristics of development leading to risk of adult onset disease. This has now been demonstrated across small and large animal models and also in the human. Most evidence of periconceptional 'programming' has emerged from maternal nutritional models but also other in vivo and in vitro conditions including assisted reproductive treatments, show consistent outcomes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 76 publications
(133 reference statements)
2
69
0
3
Order By: Relevance
“…This study further demonstrated the critical importance of the uterine environment on fetal growth and long-term consequences, consistent with the concept of developmental origins of health and disease (DOHaD) [55][56][57][58] . Epidemiological human studies have established that low birth weight is associated with increased rates of adiposity, type 2 diabetes, the metabolic syndrome, and other diseases in adult life [56][57][58][59] .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study further demonstrated the critical importance of the uterine environment on fetal growth and long-term consequences, consistent with the concept of developmental origins of health and disease (DOHaD) [55][56][57][58] . Epidemiological human studies have established that low birth weight is associated with increased rates of adiposity, type 2 diabetes, the metabolic syndrome, and other diseases in adult life [56][57][58][59] .…”
Section: Discussionsupporting
confidence: 84%
“…Epidemiological human studies have established that low birth weight is associated with increased rates of adiposity, type 2 diabetes, the metabolic syndrome, and other diseases in adult life [56][57][58][59] . This link has also been extensively investigated using animal models 57,60,61 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains impossible to this day to say which approach is superior (Mantikou et al ., 2013; Swain et al ., 2016), especially since studies in the human are made difficult by numerous confounding effects. Studies on animal models have shown that the environment surrounding oogenesis and the first steps of embryonic development influences the phenotype and can have effects during the animal's whole life (Fleming et al ., 2015), thus extending the concept of Developmental Origin of Health and Diseases (DOHaD) to the periconceptional period. These long term effects likely result from environment-induced epigenetic modifications in a sensitive period of intense epigenetic remodeling (Watkins et al ., 2008a, b; El Hajj and Haaf, 2013), leading to subsequent changes in gene expression (Burdge et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, environmental conditions experienced in early life can dramatically influence neonatal and adult biology, which may result in detrimental long-term effects (Laguna-Barraza et al 2012). There are many human and animal studies demonstrating sexual differences in response to various developmental insults during periconception (Fleming et al 2015a) and pregnancy (Sundrani et al 2017) and demonstrating sexual differences in response to various developmental insults during pregnancy (Sundrani et al 2017). However, there is a gap in knowledge of the mechanism(s) mediating environmental and maternal programing of preimplantation development.…”
Section: Introductionmentioning
confidence: 99%